Poor Accuracy of Methods Currently Used to Determine Umbilical Catheter Insertion Length - Gerdina H. Verheij; Arjan B. te Pas; Ruben S. G. M. Witlox; Vivianne E. H. J. Smits-Wintjens; Frans J. Walther; Enrico Lopriore (Hindawi Limited, 2010)
This study compares the methods of Dunn and Shukla in determining the appropriate insertion length of umbilical catheters. In July 2007, we changed our policy for umbilical catheter insertions from the method of Dunn to the method of Shukla. We report our percentage of inaccurate placement of umbilical-vein catheters (UVCs) and umbilical-artery catheters (UACs) before and after the change of policy. In the Dunn-group, 41% (28/69) of UVCs were placed directly in the correct position against 24% (20/84) in the Shukla-group. The position of the catheter-tip of UVCs in the Dunn-group and the Shukla-group was too high in 57% (39/69) and 75% (63/84) of neonates, respectively. UACs in the Dunn-group were placed directly in the correct position in 63% (24/38) compared to the 87% (39/45) of cases in Shukla-group. The position of the catheter-tip of UACs in the Dunn-group and the Shukla-group was too high in 34% (13/38) and 13% (6/45) of neonates, respectively. In conclusion, the Dunn-method is more accurate than the Shukla-method in predicting the insertion length for UVCs, whereas the Shukla-method is more accurate for UACs.